The relationship between the real effective exchange rate and non-hydrocarbon export growth - Darine Mehenna; Faiza Bouzemlal; Ali Nabil Belouard (Financial Markets, Institutions and Risks)
This study examined the impact of the exchange rate on non-hydrocarbon exports in Algeria. The main purpose of the research is to examine the relationship between the real effective exchange rate and the non-hydrocarbon export growth using the data of the Algerian economy. The data used are obtained from different sources: the real effective exchange rate is collected from International Financial Statistics published by the International Monetary Fund, while the non-hydrocarbon export growth is obtained from the Algeria Bank, and the gross domestic product variables are extracted from the official website of the World Bank. To conduct the study, the annual data for the three variables from 1980 to 2021 was considered; time series econometric techniques are used to check the existence of the relationship between variables. In the first step, the authors have performed the augmented Dickey-Fuller tests to check the stationarity of the three variables of interest. This test was computed for each variable with three models: the first model includes the constant term and the trend, the second model includes the constant term, and the third model was estimated without both the constant and the trend term. The stationary tests show that three variables (gross domestic product, the real effective exchange rate, and the non-hydrocarbon export growth) are integrated with order one, zero, and zero, respectively. In the second step, the exploration of the ARDL model between the three variables shows that the hypothesis that stipulates the existence of a significant relationship between the real effective exchange rate and the non-hydrocarbon export growth, on the one hand, is rejected, while the non-hydrocarbon export growth is, on the other hand, positively and statistically significantly correlated to the gross domestic product.